Contrast-enhanced ultrasound-guided sentinel lymph node biopsy in early-stage breast cancer: a prospective cohort study - Qiuxia Cui; Li Dai; Jialu Li; Yang Shen; Huijiang Tao; Xiaofeng Zhou; Jialei Xue (World Journal of Surgical Oncology, 2023)
Abstract Objective This study evaluated the identification efficiency of contrast-enhanced ultrasound (CEUS) for sentinel lymph nodes (SLN) to accurately represent the axillary node status in early-stage breast cancer. Method In total, 109 consecutive consenting patients with clinically node-negative and T1-2 breast cancer were included in this study. All patients received CEUS to identify SLN before surgery, and a guidewire was deployed to locate SLN in those who were successfully explored by CEUS. The patients underwent sentinel lymph node biopsy (SLNB), and the blue dye was used to trace SLN during the surgery. The decision to perform axillary lymph node dissection (ALND) depended on the intraoperative pathological identification of SLN by CEUS (CE-SLN). The concordance rate of pathological status between CE-SLN and dyed SLN was calculated. Result The CEUS detection rate was 96.3%; CE-SLN failed in 4 patients. Among the remaining 105 successful identifications, 18 were CE-SLN positive by intraoperative frozen section, and one with CE-SLN micrometastasis was diagnosed by paraffin section. No additional lymph node metastases were found in CE-SLN-negative patients. The concordance rate of pathological status between CE-SLN and dyed SLN was 100%. Conclusion CEUS can accurately represent the status of axillary lymph nodes in patients with clinically node-negative and small tumor burden breast cancer. Graphical Abstract